Media Literacy and Critical Thinking Skills Among Grade 12 Humanities and Social Sciences (HUMSS) Students in a Private Senior High School in Laguna, Philippines - Reyes, Jobelle; Baldo, Michaela; Brasino, Jessica; Saludar, Ahmillene Joy; Galicia, Leomar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between media literacy and critical thinking skills among Grade 12 Humanities and Social Sciences (HUMSS) students in a private senior high school in Laguna, Philippines. The study was anchored on Potter's Cognitive Approach, Masterman's Teaching the Media, Facione's Critical Thinking Framework, Anderson and Krathwohl's Revised Taxonomy, and Vygotsky's Sociocultural Theory, which collectively explain the development of media literacy and higher-order thinking skills. A descriptive-comparative-correlational research design was employed involving 56 Grade 12 HUMSS students selected through purposive sampling. Data were collected using a validated self-developed questionnaire that measured five dimensions of media literacy and five dimensions of critical thinking. Descriptive statistics, the Mann–Whitney U test, Kruskal–Wallis test, Shapiro–Wilk test, and Spearman's rho were used to analyze the data. The findings revealed that respondents demonstrated high levels of media literacy and critical thinking, with media access, analytical thinking, and self-regulation obtaining the highest ratings, while evaluation, interpretation, and critical assessment received comparatively lower ratings. No significant differences were found in media literacy and critical thinking across respondents' demographic and media-use characteristics. However, a significant positive relationship was identified between media literacy and critical thinking, indicating that students with stronger media literacy also exhibited higher levels of critical thinking. The study concludes that integrating media literacy into classroom instruction can strengthen students' analytical, evaluative, and responsible engagement with digital media. It recommends enhancing instruction through fact-checking, media analysis, guided discussions, debates, research tasks, and reflective learning, while future studies should involve larger, multi-institutional samples and examine additional variables. The study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting media literacy and critical thinking as essential competencies for lifelong learning and SDG 16: Peace, Justice and Strong Institutions by encouraging responsible media engagement and informed information evaluation. Its findings contribute to educational and digital sustainability by informing curriculum enhancement, instructional planning, and the development of responsible, reflective, and critically engaged learners.
Keywords: Analysis; Critical Thinking; Digital Literacy; Grade 12 HUMSS Students; Media Literacy; Media and Information Literacy; Self-Regulation; Senior High School; Social Media; Sustainable Development Goals (Sdgs)